Sphaeranthus indicus: A Promising Antimicrobial Agent - Saxena, Prasoon Kumar; Upadhyay, Shagun; Lodha, Shivani (Free Radicals and Antioxidants)
Objectives: The aim of the present study was to determine the antimicrobial property of the solvent extracts of flowers and aerial parts of S. indicus. Methods: The flowers and the aerial parts of Sphaeranthus indicus were extracted with n-hexane, benzene, chloroform, ethyl acetate and acetone respectively. The extracts were analyzed for the antimicrobial effect by disc diffusion method at concentrations of 5, 2.5 and 1.25 mg/disc. The Minimum Inhibitory Concentration (MIC) was tested using broth micro dilution method at concentrations ranging from 5 to 0.039 mg/ml. Results: There was a significant antibacterial and antifungal activity in hexane extract of flower and aerial parts. The MIC was seen at 0.15 mg/ml against Staphylococcus aureus and the highest MIC (5 mg/ml) was noted for S. epidermidis. The n-hexane extracts of flower and aerial parts showed MIC as 0.15 and 1.25 mg/ml respectively against Candida albicans. Conclusion: Concluding it can be said that the S. indicus flower n-hexane extract showed promising antimicrobial agent.
Keywords: Sphaeranthus indicus; Antibacterial activity; Minimum inhibitory concentration; Ethyl acetate; Acetone; n-hexane